FINANCIAL FEASIBILITY STUDY OF NEW EQUIPMENT INSTALLATION OF CISITU BARU NUMBER 1 BOARDING HOUSE - Jason Valentino (Journal of Social and Economics Research, 2024)
Cisitu Baru number 1 boarding house is located in Jalan Cisitu Baru number 1. Currently, this boarding house has 26 rooms with IDR 1,150,000.00 as the price of the boarding house. Moreover, this boarding house has some facilities such as wifi, bathroom inside room, bed, pillow, desk, and chair. On the other hand, this boarding house needs some replacement in bed, pillow, desk, and chair because the furniture is quite old and not worth to be used. Furthermore, the boarding house needs to install the water heater because the residents and also people who are looking for a boarding house want to have a water heater due to cold weather in Bandung. Therefore, Cisitu Baru number 1 boarding house has a plan to invest in a water heater and replace all the furniture with an increased price which is IDR 1,350,000.00 per month. This project cost about IDR 122,222,000.00 and it will be financed using 100% equity. To determine whether the project is feasible or not, it needs to calculate the feasibility study of this project using capital budgeting analysis. Based on the calculation of the capital budgeting analysis, the Net Present Value of the project is IDR 87,166,396.20 with 33% of Internal Rate of Return. Then the Payback Period is 2.71 years with 3.89 years as the Discounted Payback Period. In addition, the Profitability Index is 1.71. According to the result of all capital budgeting analysis, the project is feasible and accepted because it has a positive Net Present Value, with a 33% of Internal Rate of Return which is greater than the Weighted Average Cost of Capital, and the Payback Period is 2.71 years and 3.89 Discounted Payback Period, below the maximum Payback Period acceptance which is 10 years based on the owner preference.